Aspectos morfológicos da cloaca e do falo dos gêneros Crocodylus, Paleosuchus, Caiman e Melanosuchus (Crocodylia) com implicações evolutivas - Gustavo Leite Gonçalves (2019)
This study presents characteristics of the cloaca and the copulatory organ of the genera Crocodylus, Paleosuchus, Caiman and Melanosuchus. The amniotes cloaca exhibits a large morphological variation and is generally described as having three compartments: coprodeum is the most cranial compartment and communicates with the final part of the intestine, urodeum is the middle compartment and receives urine and semen, and the proctodeum. The cloacas of the species of Testudines and Crocodylia and the copulatory organ of Crocodylia were analyzed with the purpose of describing the morphology and investigating its possible relationship with the other cloacal structures. The studies were made from dissections and routine histological preparations. The cloaca is located in the pelvic cavity with different characteristics between Testudines and Crocodylia. In the former, the cloaca is divided in three compartments, coprodeum, urogenital sinus and proctodeum, without presenting folds that separate them. The cranial opening of the peritoneal canal is located laterally to the urogenital sinus and the canal are caudally projected into the phallus, until the caudal end of the organ. In Crocodylia, the cloaca presents coprodeum, urodeum and proctodeum the last separated by uroproctodeal fold. The cloaca presents histological similarities between the rectum and the coprodeum and between the urodeum and proctodeum. In the region of the urodeum is the genital sinus, a characteristic of the Crocodylia cloaca. The cranial opening of the peritoneal canal is located laterally to the coprodeum and the canal extends caudally until it ends in a papilla, of different formats and location, in the body of the phallus. The phallus of Crocodylia species has a vascular body, a fibroelastic body and an erectile tissue. The phallus is protracted by the action of the cloacal muscles and retracted from the action of the elastic ligament that is inserted in the ventral process of the body of the phallus and in the ischium. The papilla with the peritoneal canal is a synapomorphy of Crocodylia and the elastic ligament is a character shared by Crocodylia and Paleognathae birds that have an eversible phallus.